The small mammal community of the marshy meadows in the Ljubljansko barje area (Yugoslavia) - Tomi Trilar (Acta Biologica Slovenica)
Spring and autumn population densities and biomasses of small mammals were estimated by the removal standard minimum method during two consecutive years (1985-1986) in the marshy meadows of the Ljubljansko barje (NW Yugoslavia). Ten species of insectivores and rodents were recorded: Neomys fodiens, Neomys anomalus, Sorex araneus, Crocidura leucodon, Clethrionomys glareolus, Pilymys subterraneus, Microtus arvalis, Micro/us agreslis, Apodemus sylvaticus, and Apodemus flavicollis. M. arvalis was subdominant in 1985. M. agreslis and S. araneus were euconstant species. Population densilies in spring were between 29,7 and 101,7 ind./ha, and 253/7 ind./ha in autumn. Biomasses were between 632 and 2756 g/ha in spring and 4693 g/ha in autumn.